2009
DOI: 10.1590/s1413-70542009000700064
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade polínica como seleção assistida no programa de melhoramento genético de triticale

Abstract: RESUMONeste trabalho,objetivou-se analisar a viabilidade de grãos de pólen de 52 genótipos de triticale, oriundos do bloco de cruzamentos do programa de melhoramento genético da Embrapa Trigo do ano de 2005. A coleta das espigas foi realizada quando as plantas se encontravam na fase anterior à antese. As análises citológicas foram realizadas fixando as anteras de uma mesma espiga em fixador Carnoy. Para a análise polínica, as lâminas foram confeccionadas usando-se três anteras da mesma flor, oriundas das regiõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
1
6
0
3
Order By: Relevance
“…This occurs because some meiotic abnormalities only have an effect during the germination stage and do not influence pollen viability (Junqueira Filho et al, 2003). Similar results have been reported for other genotypes of hexaploid triticale (Rosa et al, 2006;Zanotto et al, 2009).…”
Section: Meiotic Index and Pollen Viabilitysupporting
confidence: 90%
“…This occurs because some meiotic abnormalities only have an effect during the germination stage and do not influence pollen viability (Junqueira Filho et al, 2003). Similar results have been reported for other genotypes of hexaploid triticale (Rosa et al, 2006;Zanotto et al, 2009).…”
Section: Meiotic Index and Pollen Viabilitysupporting
confidence: 90%
“…However, in virtue of being practical and fast, they can rapidly generate additional information that may orientate breeders in their choice of genitors, in works involving controlled pollinations. Acetocarmine and propionic carmine are the most used dyes to determine pollen viability, also in routine analyses (Zanotto et al, 2009). In another study using two hybrids between B. ruziziensis and B. brizantha, these same authors observed less than 35% of viable pollen grains, as well as meiotic abnormalities such as irregular chromosome segregation, chromosome adherence and abnormal cytokinesis, which probably affected the viability of the pollen (Risso-Pascotto et al, 2005a).…”
Section: Resultsmentioning
confidence: 99%
“…Studies using acetocarmine 1% in 52 genotypes of Triticale, an intergeneric hybrid originated from crossing between tetraploid wheat and diploid rye, showed that the average percentage of viable pollen grains in the genotypes ranged from 68.6% to 98.8%. These values are considered high among genetically distinct genotypes (ZANOTTO et al, 2009). Acetocarmine 1% and propionic carmine 1% are widely used in routine analysis; however, they may be inadequate for some species, as thick exine of pollen grains can hamper dye penetration.…”
Section: Resultsmentioning
confidence: 99%